Using SSR markers for assessment genetic diversity and detection drought escape candidate genes in barley lines (Hordeum vulgare L.) - Gougerdchi, Vahideh; Dezhsetan, Sara; Ebrahimi, Mohammad Ali; Sadeghzadeh, Behzad; Savari, Sona (Plant Breeding and Seed Science, 2014)
Assessment of genetic diversity using molecular markers is one of the primary and important steps in breeding programs. In this study, genetic diversity of 52 barley lines evaluated using 68 SSR primer pairs and 47 primer pairs produced clear and polymorphic banding pattern. In general, 153 polymorphic alleles de-tected. The number of observed polymorphic alleles varied from 2 to 9, with an average of 3.26 alleles per locus. Polymorphic Information Content (PIC) ranged from 0.07 to 0.81, with an average of 0.45. In this research, SSR markers differentiated the studied lines efficiently. Using cluster analysis, studied barley lines divided into two groups. Genetic diversity was relatively corresponding with geographical origins, because the lines related to a country somewhat diverged from each other. Two-rowed Iranian and Chinese barleys classified in one subgroup. Also, most six-rowed barleys classified in one subgroup. Association mapping analysis was used to identify candidate genes for drought escape in barley lines and 16 informative markers were identified after which confirmation in other tests could be suitable for marker assisted breeding drought escape.